The Hypomorphic Variant p.(Gly624Asp) in COL4A5 as a Possible Cause for an Unexpected Severe Phenotype in a Family With X-Linked Alport Syndrome - Macheroux, Eva Pauline; Braunisch, Matthias C.; Pucci Pegler, Stephanie; Satanovskij, Robin; Riedhammer, Korbinian M.; Günthner, Roman; Gross, Oliver; Nagel, Mato; Renders, Lutz; Hoefele, Julia (Frontiers in Pediatrics, 2019)
Background: Alport syndrome (AS) is a progressive kidney disorder leading to end stage renal disease (ESRD). Extrarenal symptoms like hearing loss and ocular changes can be observed. Approximately 85% of the patients carry pathogenic variants in COL4A5 (X-linked inheritance). The variant c.1871G>A, p.(Gly624Asp) in COL4A5 is described in the literature as a hypomorphic variant associated with thin basement membrane nephropathy. ESRD was only seen rarely at a median age of 50 years and extrarenal manifestations have only been described in single cases. Case report & Methods: This is a report on a family with X-linked AS. In the index female patient, microscopic hematuria and proteinuria were observed beginning at the age of 20 years and 41 years, respectively. Microscopic hematuria was also present in the daughter (from 6th month of life), the son (from 22nd month of life), the mother and the maternal grandniece. Proteinuria was observed in the maternal aunt and paternal grandmother. The father of the index patient, a paternal uncle and a second cousin presented ESRD at the age of 49, 34 and 70 years of life, respectively. Extrarenal manifestations were absent in the whole family. In the index patient, her children and her mother molecular diagnostics were performed using Sanger and exome sequencing. Results: In all examined family members the variant c.1871G>A, p.(Gly624Asp) in COL4A5 was identified. With the exception of the index patient, who was homozygous for this variant, all family members carried the variant heterozygously or hemizygously. A different or additional monogenic hereditary nephropathy could not be detected by exome sequencing of the index patient. Discussion: This is the first report of a patient with the variant p.(Gly624Asp) in COL4A5 in a homozygous state. The variant was previously reported as a mild variant requiring dialysis in less than 10%. The family presented, however, with a severe clinical course. We therefore suggest to question the term “hypomorphic” in the context of the variant p.(Gly624Asp) although molecular diagnostics could not be done in all affected family members.